INFORMATION POUR LA PRISE DE DÉCISION DANS LES STRUCTURES CERTIFIÉES ISO 9001 VERSION 2008: PERCEPTION DE L’INFORMATION FORMELLE ET INFORMELLE PAR LES GESTIONNAIRES (ÉTUDE DE CAS) - El Idrissi, Hicham; Barrijal, Said; Kerak, Ebrahim; Chefchaouni, Al mountacer Charif (European Scientific Journal, ESJ, 2015)
In the field of Managerial Work Job and Behaviors (MWJB), many research studies have focused on managerial behavior in the workplace. Several models have thus been developed. They all described a particular way of manager’s real work. With the quality movement, many managers adopt the quality management approach. They aim to improve organizational image, management, communication… But also find themselves having to follow a certain style of management. The question that arises is: will these managers really adopt the quality management style? In this paper, we present an empirical study which aims to answer this question. The field of this research was limited to « management of information for decision making ». And we choose Mintzberg’s model as reference of MWJB. By using a case study of two Moroccan public institutions certified ISO 9001 version 2008, we examined the manager’s perception towards formal and Informal information. The main result found that information coming from the quality Management System ISO 9001 (QMS) is very much appreciated by managers. We also found that the QMS had to a certain extent modified manager’s perception towards formal and informal information. However, regarding different kinds of formal and informal information, the general order of manager’s information preferences is dictated by other factors, notably the synthetic and the opposable character of information. Also, it was found that certain managerial preferences, such as e-mail, could be used more to maximize the returns of the QMS.